Effects of physical activity and melatonin on brain‐derived neurotrophic factor and cytokine expression in the cerebellum of high‐fat diet‐fed rats - Ai Sugiyama; Hisashi Kato; Hisashi Takakura; Seita Osawa; Yuki Maeda; Tetsuya Izawa (Wiley, 2020)
Abstract Aims Obesity suppresses brain‐derived neurotrophic factor (BDNF) expression and increases the expression of pro‐inflammatory cytokines. Herein, we assessed whether exercise training (ET), melatonin administration (MT), or their combination can affect the expressions of BDNF and cytokines in the cerebellum of high‐fat diet (HFD)‐fed rats. Methods Wistar rats (4 weeks old) were divided into five groups: normal diet (ND)‐fed control (ND‐SED), HFD‐fed control (HFD‐SED), HFD‐fed ET (HFD‐ET), HFD‐fed MT (HFD‐MT), and HFD‐fed MT plus ET (HFD‐ETMT) group. The rats were fed ND or HFD for 17 weeks. Rats were subjected to ET (running on a treadmill) and/or MT (melatonin 5 mg/kg body weight, i.p.) for 9 weeks, 8 weeks after beginning the diet intervention. Changes in BDNF and cytokine expression levels were determined using immunoblotting and cytokine arrays, respectively, 36 hours following the last bout of ET. Results Neither HFD‐ET nor HFD‐MT rats exhibited enhanced BDNF expression in the cerebellum, but HFD‐ETMT rats had higher level of BDNF expression compared with the others. The expression of TrkB, a BDNF receptor, was higher in HFD‐ETMT rats than in HFD‐ET and HFD‐MT rats. HFD enhanced the expression of interleukin (IL)‐1, IL‐2, and interferon‐γ but reduced the expression of IL‐4, IL‐6, and IL13. ET and ET plus MT counteracted these HFD‐induced changes in cytokine expressions. Conclusion Exercise in combination with melatonin confers the potential benefits of increasing BDNF and improving HFD‐induced dysregulations of cytokines in the cerebellum.